Conservative treatment of Angle Class III malocclusion with anterior crossbite - João Hélder Ferreira de Aguiar (Dental Press Editora, 2015)
Angle Class III malocclusion is characterized by anteroposterior dental discrepancy which might be associated or not with skeletal changes. Class III molar relationship is associated with vertical or lingually tipped mandibular incisors and a usually concave profile. These characteristics seriously affect facial esthetics and most frequently are the reason why patients seek orthodontic treatment. This case was presented to the committee of the Brazilian Board of Orthodontics and Facial Orthopedics (BBO) as part of the requisites to become a BBO Diplomate.